Between Rules and Freedom: Rawls and Illich on the Role of Institutions in Society - Vrdoljak, Jana (Analiza: časopis za kritično misel, 2025)
The article compares Illich’s and Rawls’s understanding of the role of institutions in shaping a just social order and ensuring individual autonomy. Rawls regards social institutions as the essential foundation of a just and stable societal structure, while Illich highlights their limitations, particularly concerning legitimacy and political, ideological, and economic neutrality. According to Illich, institutions can threaten individual freedom when they shift from being the means for achieving goals to becoming ends in themselves. As an alternative, he proposes a convivial community that rejects tools – namely systems, technologies, and institutions – that could degenerate into mechanisms of control or restrictions on freedom. However, even this solution is not without risks, as it may fall into the same problems as institutions by adopting certain forms of control and restriction characteristic of traditional communities. Despite these limitations, Illich’s critique underscores the need for institutional reform to ensure that they truly serve the protection of individual freedom and autonomy.
Keywords: Illich; Rawls; social institutions; liberty; justice; individual autonomy